Promosi digital, daya tarik iklan, citra merek, dan strategi tagline gratis ongkir dalam mendorong keputusan pembelian generasi Z di Tokopedia - Taufiq, Yudi Muahamad; Cahya, Handy Nur; Aryanto, Vincent Didiek Wiet; Anomsari, Ariati (Journal of Management and Digital Business, 2025)
Advancements in information technology have accelerated the growth of online marketplaces, creating intense competition among e-commerce platforms in Indonesia. Generation Z, as a digital-native consumer group, represents a crucial segment to understand in the context of online shopping behavior. This study aims to evaluate the factors influencing Generation Z’s purchasing decisions on Tokopedia, focusing on promotion, advertising appeal, brand image, and the “free shipping” tagline. A quantitative research approach was employed using a survey of 106 respondents. The data were analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS 4. The results reveal that promotion, brand image, and the “free shipping” tagline have a significant positive effect on purchasing decisions, while advertising appeal does not show a significant influence. These findings provide new insights into enhancing the effectiveness of marketing strategies in responding to Generation Z’s preferences in the digital era. The study’s implications highlight the importance for Tokopedia to strengthen its brand image, maintain consistent promotional strategies, and continue leveraging the “free shipping” tagline as a core marketing strategy.